Negotiating Learner Autonomy in a Cross-cultural, Emancipatory Academic Environment: An Autoethnographic Study - Nguyễn, Huy Cường (Nordic Journal of Comparative and International Education (NJCIE), 2025)
In an era of accelerating globalization, an increasing number of scholars cross national borders and accumulate international academic experiences, presenting both opportunities and challenges. This autoethnography examines the challenges I, a Vietnamese PhD student, encountered while navigating learner autonomy within a cross-cultural, emancipatory academic environment in the US. Drawing on my retrospective narrative, in-depth interviews with my academic advisor, and a reflective journal, I narrate my journey of negotiating the newly found freedom in a PhD program driven by emancipatory pedagogy. The process reveals learner autonomy as a complex, non-linear negotiation shaped by different environmental factors, especially the roles of my academic advisor. Thanks to the development of learner autonomy, I slowly turned into an independent scholar, but the process prompted critical reflections on the tension between my traditional Confucian Heritage Culture (CHC) values and the newly acquired emancipatory ideals. The paper may help international PhD students to better navigate their studies in new cultural and academic environments. It may also help PhD supervisors, including those in Nordic countries, become more aware of potential challenges and develop alternative strategies for working with doctoral students from different cultural backgrounds. Finally, it may offer insights into how a more emancipatory academic environment might be reimagined in CHC contexts.